Performance Evaluation of BD Phoenix NMIC-413 Antimicrobial Susceptibility Testing Panel for Imipenem, Meropenem, and Ertapenem Against Clinical Carbapenem-Resistant and Carbapenem-Susceptible Enterobacterales - Zhang, Jingjia; Jia, Peiyao; Zhu, Ying; Zhang, Ge; Xu, Yingchun; Yang, Qiwen (Frontiers in Medicine, 2021)
Abstract Purpose: The carbapenem-resistant Enterobacterales (CRE) has become a major clinical and healthcare problem worldwide. Screening methods have been extensively developed but still need improving (e.g., tests with accurate and simple minimum inhibitory [MICs]). In this study, the performance of the BD Phoenix NMIC-413 AST panel was evaluated against clinical CRE and carbapenem-susceptible Enterobacterales (CSE) in China. The panel was evaluated the first time in the Chinese clinical lab. Methods: Antimicrobial susceptibility testing of 303 clinical Enterobacterales isolates was conducted by using broth microdilution (BMD), Phoenix NMIC-413 AST panel, and disc diffusion method for imipenem, ertapenem, and meropenem. Considering BMD as a gold standard, essential agreement (EA), categorical agreement (CA), minor error (MIE), major error (ME), and very major error (VME) of the other two methods were determined according to CLSI guidelines. CA and EA > 90%, ME < 3%, and VME < 1.5% were considered as acceptable criteria. Polymerase chain reaction and sanger sequencing were performed to determine the β-lactamase genotypes of CRE isolates. Results: Enrolled isolates included 195 CREs and 108 CSEs according to the BMD-MIC values of three carbapenems. Tested CREs included 100 blaKPC-2-positive organisms, 31 blaIMP-positive organisms, 28 blaNDM-positive organisms, 5 blaVIM-positive organisms, 2 both blaIMP and blaVIM-positive organisms, 2 blaOXA-48-positive organisms, and 27 isolates without carbapenemase genes. For the Phoenix NMIC-413 method, CA and EA rates were > 93%, MIE rates were < 5%, ME rates were < 1.75%, and VME rates were 0%, across the three drugs. For the disc diffusion method, the CA rates for three drugs were all > 93%, while the MIE and ME rates were all < 5% and < 3% respectively. VME rate was 3.28% for imipenem, exceeded the cut-off value specified by CLSI M52, 0% and 0.56% for ertapenem and meropenem, separately. Conclusion: Based on the genomic data, the detection of CRE and CSE was more reliable using the BD Phoenix NMIC-413 panel compared to the BMD and disc approaches. Therefore, our study supports the use of BD Phoenix NMIC-413 panel as a suitable alternative to BMD for the detection of carbapenem resistant isolates in a clinical setting.